Synthesis and thermal study on viscose rayon succinate coupled with metals and viscose rayon succinic silane - Khasbaatar, Aruukhan Dashkhuu; Chun, Yong Jin; Choi, Ung Su (ELSEVIER SCIENCE INC, 2007)
In this article, synthesis of viscose rayon succinate (VRS), viscose rayon succinic silanate (VRSS) and viscose rayon succinate with metal complexes were confirmed by C-13 solid state nuclear magnetic resonance (NMR) spectroscopy and Fourier transform infrared (FT-IR) spectroscopy. Thermal properties of the synthesized materials were studied with thermogravimetric analysis (TGA) and limited oxygen index (LOI) testing. VRS was less stable than viscose rayon (VR) at high temperatures. However, weight residues of metal complexed VRS increased in comparison to VR and VRS after char formation at high temperatures. The amount of weight residue could be described in the following order: VRS-Cu > VRS-Cr > VRS-Al > VRS-Ni > VR > VRS. All of the materials were found to be effective as flame retardants.